Do Smallholder Farmers Need Nutrition Education? ACase Study from KwaZulu Natal, South Afric - Sarahi Morales; Abdukladir A. Egal; Wilna Oldewage-Theron (Journal of International Agricultural and Extension Education, 2021)
South Africa (SA) is considered as the second largest economies in Africa with well-developed agricultural food production system. But food security is still a challenge at household level. Currently, in Africa, smallholder agriculture is recognized to contribute food security at household level. This study investigates the prevalence of food insecurity and nutritional knowledge of 78 local smallholder farmers in KwaZulu Natal (KZN) province of South Africa. The results from this study indicated that nutrition knowledge was poor and food insecurity was prevalent at >40% at the household level. It is therefore recommended that future agricultural training should include nutrition education based on FBDG (Food Based Dietary Guidelines) in their respective programs so as to attain a balanced diet for healthy and productive smallholder farmer communities.
Keywords: smallholder farmers; food security; nutrition knowledge; South Africa